KETERLIBATAN ANAK MUDA KOTA BEKASI DALAM KEBIJAKAN SMART CITY - Elvira Suryani (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2023)
Smart City is a big issue in the world and Indonesia that focuses on the involvement of the active roleof the community in city development using a centric approach. This is done by the government to beone of the solutions to solve various problems that occur in urban areas. The concept of Smart City hasbeen implemented in several major cities in Indonesia such as Jakarta, Bandung, Surabaya, and Bekasione of them. The background of this research is based on the concept of a Smart City which is also inline with the vision and mission of Bekasi City, namely to